2019
DOI: 10.3390/scipharm87030023
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the In Vitro Anti-Intravasative Properties of Flavonoids

Abstract: We investigated the effect of 21 flavonoids in a three-dimensional in vitro system for their ability to inhibit gap formation by MCF-7 breast cancer spheroids in monolayers of lymphendothelial cells. Different representatives of the classes of flavones, flavonols, and flavanones were tested in the circular chemorepellent-induced defects (CCID)-assay. Bay11-7082, a known inhibitor of CCID formation served as the positive control. This study provides the first comparison of the potential of flavonoids to suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…2 B). These results are consistent with reports that the flavonoid Luteolin inhibited invasion of MDA-MB-231 cells by upregulating E-cadherin and downregulating the mesenchymal markers vimentin, N-cadherin, SNAIL and SLUG ( Eichsteininger et al, 2019 ). Together, the data showed that KB2 exhibited several anti-breast cancer properties.…”
Section: Resultssupporting
confidence: 93%
“…2 B). These results are consistent with reports that the flavonoid Luteolin inhibited invasion of MDA-MB-231 cells by upregulating E-cadherin and downregulating the mesenchymal markers vimentin, N-cadherin, SNAIL and SLUG ( Eichsteininger et al, 2019 ). Together, the data showed that KB2 exhibited several anti-breast cancer properties.…”
Section: Resultssupporting
confidence: 93%
“…Consistent with earlier results in a MCF7/LEC model [ 6 ], the 2-phenyl-5,7-dihydroxy-chromen-4-one structure of flavones without any additional substitution in positions 6 or 8 seems essential for the effects in all three 3D models and the IC 50 values of the most active substances apigenin, acacetin, luteolin and chrysin were in a comparable dimension.…”
Section: Discussionsupporting
confidence: 89%
“…In an earlier study, flavanones remained without any effects in a similar CCID model for breast cancer based on MCF7/LEC cells [ 6 ]. Surprisingly, in the here presented colon cancer models, the flavanone pinocembrin was weakly active in the LEC model and, although categorized as inactive, showed an IC 50 of 78.3 µM in the BEC model ( Supplemental Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations